Community Service-Based Accounting Education for Sustainable Financial Development in Luxembourg - Achen Karriel (Journal of Conflict and Social Class (JCSC), 2024)
The rapid advancement of financial systems and digital accounting technologies has increased the importance of accounting literacy and financial awareness in contemporary society. Accounting education is considered an essential strategy for improving financial management competence, responsible economic behavior, and sustainable financial development within communities. This community service program aims to strengthen financial awareness through community service-based accounting education in Luxembourg. The program employed a qualitative participatory approach involving students, workers, entrepreneurs, and community members through workshops, mentoring activities, accounting simulations, and collaborative learning sessions. Participants were introduced to budgeting techniques, bookkeeping practices, financial reporting systems, digital accounting applications, and ethical financial management principles to improve accounting competence and financial responsibility. The results demonstrated that participants experienced significant improvement in accounting literacy, budgeting competence, financial recording abilities, and confidence in managing financial information systematically. In addition, collaborative educational activities encouraged active participation, analytical thinking, and awareness regarding financial transparency and accountability. The integration of digital accounting education also strengthened participants’ technological adaptability and understanding of modern financial management systems. Despite challenges related to differences in educational backgrounds, technological familiarity, and accounting understanding, continuous mentoring and participatory educational approaches contributed positively to the implementation process. Overall, community service-based accounting education provided valuable opportunities for improving financial awareness, strengthening community economic resilience, and supporting sustainable financial development in Luxembourg. The collaborative educational approaches implemented in this program can also serve as important references for developing accounting literacy and financial empowerment programs in various educational and social contexts worldwide.